The tadpole of Sphaenorhynchus caramaschii, with comments on larval morphology of Sphaenorhynchus (Anura: Hylidae) - Araujo-Vieira, Katyuscia; Tacioli, Andre; Faivovich, Julian; Orrico, Victor G. D.; Grant, Taran (Zootaxa, 2015)
We describe the tadpole of Sphaenorhynchus caramaschii. It differs from tadpoles of other species of Sphaenorhynchus in having a short spiracle, submarginal papillae, and alternating short and large marginal papillae in the oral disc. Some larval characteristics, like morphology and position of the nostrils, length of the spiracle, and size of the marginal papillae on the oral disc are discussed for tadpoles of other species of Sphaenorhynchus.